KERJASAMA INDONESIA-UNITED NATION WORLD FOOD PROGRAMME DALAM MENGATASI MASALAH KETAHANAN PANGAN DI NUSA TENGGARA TIMUR MELALUI INDONESIA COUNTRY PROGRAMME TAHUN 2016-2020 - Dessiana Nurul Fitri, (2021)
The spread of food problems in Indonesia and the global world makes food security an important issue to be resolved. Because food itself is a pillar of human resource development. Food problems in Indonesia are faced by the Central Government and also Regional Governments caused by inequality in aspects of food security such as Food Availability, Access to Food, and Food Utilization which must be resolved to achieve sustainable development goal number 2, namely zero hunger. From year to year, NTT Province is one of the provinces experiencing poor food security problems, so special attention is needed to NTT Province. Therefore, Indonesia cooperates with the World Food Program as an international organization tasked with helping countries experiencing food problems to solve food security problems in the province of NTT. Concerning this cooperation, Indonesia and WFP cooperate under the Indonesia Country Program as the basis for the design of the implementation of the cooperation. In this study, the Indonesia Country Program carried out is for the 2016-2020 period. The collaboration is carried out through the formation of National and Provincial Food Security and Vulnerability Maps, Maternal and Child Nutrition Programs (KIA), School Children Nutrition Programs (PROGAS), Cash and Vouchers as well as disaster response programs. In addition, WFP has also assisted Indonesia in preparing the National Action Plan for Food and Nutrition (RAN-PG) as well as the Regional Action Plan for Food and Nutrition (RAD-PG). This collaboration is carried out to solve the food problem in NTT Province and also achieve sustainable development goal number 2, namely zero hunger. This study uses the theory of international cooperation, the concept of food security as well as the concept of sustainable development goals and qualitative research methods.